Analisis Keselamatan Dan Kesehatan Kerja Pada PT. Ethica Industri Farmasi - Dikha Septiani Dewi; Sungkono Sungkono (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
One of the problems in the world of industrial work is work accidents. Occupational accidents have a negative impact on workers who experience and do not experience. For partners and for the company itself. So there must be a good application of occupational safety and health (K3) to overcome it. The purpose of this research is to explain the application of Occupational Safety and Health at PT. Pharmaceutical Industry Ethics. This research was conducted with a qualitative descriptive method. Data obtained from interviews with one of the staff and also employees at PT. Pharmaceutical Industry Ethics. Documentation is carried out on documents regarding company profiles and other supporting documents. data analysis is done by giving meaning to the data collected and finally a conclusion is drawn.